The LinKin System: A new robotic and universally applicable radiation therapy device - Ziegler, Christian; Franke, Jörg (2013 44th International Symposium on Robotics, ISR 2013, 2013)
This paper presents the LinKin System, a fundamentally new robotic radiation therapy device with six degrees of freedom. Because of its linear kinematics system design it has substantial advantages over common therapy devices. The highly flexible and universally applicable LinKin System opens a unique broad application range. Furthermore, due to its novel assistant functions it can be well-integrated into the clinic specific workflows. © 2013 IEEE.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Mechanisms and Kinematics; Medical Robots; Radiation Therapy